Case report: First evidence of impressive efficacy of modulated dose selpercatinib in a young Caucasian with ANK3-RET fusion-positive NSCLC - De Carlo, Elisa; Bertoli, Elisa; Schiappacassi, Monica; Stanzione, Brigida; Del Conte, Alessandro; Doliana, Roberto; Spina, Michele; Bearz, Alessandra (Frontiers in Oncology, 2024)
Over the past decade, molecular characterization has led to change the management of advanced non-small cell lung cancer (NSCLC) harboring driver mutations. Rearranged during transfection (RET) gene fusions, occurring in 1% to 2% of NSCLC, have emerged as an oncogenic druggable target. Systemic targeted therapies with highly selective RET inhibitors (RETi), selpercatinib and pralsetinib, represent a recent clinical breakthrough. Whilst the development of RETi has improved survival, with their increasing use, it is crucial to be aware of the risks of rare but serious adverse events (AEs). A particular challenge for clinicians in applying targeted therapies is not only diagnosing but also interpreting rare mutations. Herein, we report a case of a 43-year-old Caucasian advanced NSCLC patient diagnosed with a rare RET gene fusion, ANK3::RET, identified with Next Generation Sequencing (NGS). Selpercatinib has been initiated at the recommended initial dose after one incomplete chemotherapy cycle due to a severe infusion reaction, but it subsequently required a dose adjustment following grade 3 (G3) AEs. During treatment, we used a particular selpercatinib dosage (160 mg in the morning and 80 mg in the evening) with good tolerance and without compromising effectiveness. Our finding broadens the range of RET fusion types in not-Asian NSCLC. To the best of our knowledge, our case demonstrates, for the first time, a clinical and radiological response to frontline highly selective RETi selpercatinib, expanding the spectrum of potential oncogenic RET fusion partners in newly diagnosed NSCLC patients. Furthermore, to our knowledge, this is the first case describing a RET fusion-positive (RET+) NSCLC patient treated with a modified selpercatinib dosage outside the drug data sheet and demonstrating a safe and effective use.